Code-Switching in Indonesian Youtube Vloggers: A Sociolinguistic Analysis - Musaropah Musaropah (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The development of digital platforms has significantly transformed linguistic practices, particularly through the phenomenon of code-switching among content creators. This study aims to analyze the patterns, reasons, and functions of language use in the vlogs of Boy William, Sasha Marissa, and Fathia Izzati. Employing a qualitative descriptive method, this research is grounded in the theoretical frameworks of Poplack (1980), Grosjean (1982), and Holmes (2013). The findings reveal a total of 144 instances of code-switching, with the inter-sentential type emerging as the most dominant pattern. The analysis indicates that code-switching functions as a systematic communication strategy that facilitates lexical efficiency and enhances emotional expression. Furthermore, the practice operates as symbolic capital for vloggers, enabling them to construct a distinctive digital identity while simultaneously negotiating their social position and hybrid identity within a complex global digital space. Thus, code-switching is not merely a linguistic phenomenon but also a strategic tool in online interaction and self-presentation.